INDONESIAN POWER OF ATTORNEY AND ITS POLISH TRANSLATION – SELECTED ISSUES AND TRANSLATION PROBLEMS - ZOZULA, Daria (Comparative Legilinguistics, 2016)
The purpose of this paper is to analyze and compare authentic texts of Indonesian powers of attorney to sell real estate with its polish translation. The analysis starts with the definition of parallel texts and explanation of the research method. The author has chosen six most interesting clause, the ones that are potentially problematic and feature issues related to the differences in the legal systems or languages of both countries. The ending conclusion is that differences between the morphology and grammar of Polish and Indonesian as well as differences between the legal systems may be the source of translation problems. The subject of Polish-Indonesian comparative legilinguistics is vast and should be further researched into.